2020
DOI: 10.12660/rda.v279.2020.81376
|View full text |Cite
|
Sign up to set email alerts
|

Measuring efficiency of Brazilian courts: one decade later

Abstract: <p><span>Medindo a eficiência dos tribunais brasileiros: uma década depois</span></p><p><span><br /></span></p><p><span>ABSTRACT<br />The Judiciary is perhaps one of the most scrutinized political institutions in Brazil. Its credibility, independence and efficiency are considered to have crucial impacts on social, politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Performance is also a multidimensional and multilevel construct, which has been observed in the most diverse public organizations under varied aspects. With regard to Justice Organizations, performance has been linked to: speed of judicial proceedings (e.g., Abramo, 2010), workload and output (e.g., Beenstock & Haitovsky, 2004;Jonski & Mankowski, 2014), efficiency (e.g., Yeung, 2020), access to justice (e.g., Cunha, Oliveira, & Glezer, 2014;Oliveira & Cunha, 2016), quality, and effectiveness (Gomes & Guimarães, 2013). In the present study, performance is observed through the perception of bureaucrats about the results and policies produced by the PDO.…”
Section: Autonomy and Performance Of Pdosmentioning
confidence: 99%
“…Performance is also a multidimensional and multilevel construct, which has been observed in the most diverse public organizations under varied aspects. With regard to Justice Organizations, performance has been linked to: speed of judicial proceedings (e.g., Abramo, 2010), workload and output (e.g., Beenstock & Haitovsky, 2004;Jonski & Mankowski, 2014), efficiency (e.g., Yeung, 2020), access to justice (e.g., Cunha, Oliveira, & Glezer, 2014;Oliveira & Cunha, 2016), quality, and effectiveness (Gomes & Guimarães, 2013). In the present study, performance is observed through the perception of bureaucrats about the results and policies produced by the PDO.…”
Section: Autonomy and Performance Of Pdosmentioning
confidence: 99%
“…O desempenho também é um construto multidimensional e multinível, que tem sido observado nas mais diversas organizações públicas sob diversos aspectos. No que diz respeito às organizações da Justiça, o desempenho tem sido associado a: celeridade dos processos judiciais (e.g., Abramo, 2010), carga de trabalho e produtividade (e.g., Beenstock & Haitovsky, 2004;Jonski & Mankowski, 2014), eficiência (e.g., Yeung, 2020), acesso à justiça (e.g., Cunha, Oliveira, & Glezer, 2014;Oliveira & Cunha, 2016), qualidade, e efetividade (Gomes & Guimarães, 2013). No presente estudo, o desempenho é observado por meio da percepção dos burocratas sobre os resultados e as políticas produzidas pela DP.…”
Section: Autonomia E Desempenho De Dpsunclassified